Modification of natural oil sorbent for improvement of hydrophobicity - Vaišis, Vaidotas; Anužytė, Eglė; Paliulis, Dainius; Bradulienė, Jolita (Journal of Environmental Engineering and Landscape Management, 2022)
A sorbent made of natural materials (moss) was selected for the sorption of diesel from the surface of the water. The sorbent was modified to increase its hydrophobic–oleophilic characteristics. Typical natural organic sorbent from moss was selected and modified in three different ways: processed with hot water (80 °C and 100 °C), mercerized and coated with oil–water (10% and 50%). Water, diesel sorption capacity, and oil retention tests were performed. Tests showed that simple treatment with hot water and alkali can change surface properties and improve sorption capacity. Modification with hot water at 80 °C enhanced sorbents’ oil sorption capacity and showed the best results but meanwhile, this method readily increased hydrophilicity. This method of sorbent treatment could not be applied in cases where sorbents are used to clean oil spills from water surfaces. Meanwhile, better sorption results would be obtained in cases where cleaning operations take place on soil and other solid surfaces.